Epichloë Endophytes Shape the Foliar Endophytic Fungal Microbiome and Alter the Auxin and Salicylic Acid Phytohormone Levels in Two Meadow Fescue Cultivars - Mathew Suni Anie; Helander Marjo; Saikkonen Kari; Vankova Radomira; Dobrev I Petre; Dirihan Serdar; Fuchs Benjamin (MDPI, 2025)
Plants harbor a large diversity of endophytic microbes. Meadow fescue (Festuca pratensis) is a cool-season grass known for its symbiotic relationship with the systemic and vertically—via seeds—transmitted fungal endophyte Epichloë uncinata, yet its effects on plant hormones and the microbial community is largely unexplored. Here, we sequenced the endophytic bacterial and fungal communities in the leaves and roots, analyzing phytohormone concentrations and plant performance parameters in Epichloë-symbiotic (E+) and Epichloë-free (E-) individuals of two meadow fescue cultivars. The endophytic microbial community differed between leaf and root tissues independent of Epichloë symbiosis, while the fungal community was different in the leaves of Epichloë-symbiotic and Epichloë-free plants in both cultivars. At the same time, Epichloë symbiosis decreased salicylic acid and increased auxin concentrations in leaves. Epichloë-symbiotic plants showed higher biomass and higher seed mass at the end of the season. Our results demonstrate that Epichloë symbiosis alters the leaf fungal microbiota, which coincides with changes in phytohormone concentrations, indicating that Epichloë endophytes affect both plant immune responses and other fungal endophytes. Whether the effect of Epichloë endophytes on other fungal endophytes is connected to changes in phytohormone concentrations remains to be elucidated.